Digital Human Capital and MSME Competitiveness in Makassar City: Qualitative Study of Competitiveness, Mindset, and Digital Transformation - Burhanuddin (Malaqbi Publisher, 2025)
This qualitative study investigates how micro, small, and medium enterprises (MSMEs) in Makassar develop digital human capital—a composite of technical skills, cognitive orientations, and socio-digital practices that enable entrepreneurs to adapt, innovate, and compete in the digital economy. Using semi-structured interviews, participant observation, and document analysis with 14 MSME owners across food, fashion, craft, and service sectors, the research applies an interpretive framework to uncover the social processes underlying digital capability formation. The findings reveal four interlocking themes: (1) layered digital competencies, characterized by progressive mastery through trial and error; (2) growth mindsets and pragmatic optimism, fostering resilience amid technological disruption; (3) learning ecosystems and social scaffolding, where peer groups, local incubators, and online communities co-create knowledge; and (4) digital human capital as relational competitive leverage, where digital trust and responsiveness strengthen market relationships. The study concludes that digital transformation in MSMEs is not merely technological but deeply social and moral, requiring policies that prioritize continuous learning, inclusive access, and ecosystem responsibility. By framing competitiveness as a relational and sustainable outcome, the research contributes to human-centered digital economy theory and offers actionable insights for policymakers, educators, and entrepreneurs in developing urban contexts.